Hubungan Jenis Pestisida Berdasarkan Kandungan Senyawa Aktif yang Digunakan terhadap Kadar Timbal (Pb) dalam Darah Petani di Kabupaten Bangka: The Correlation Between Pesticides Type Based on the Content of the Compounds Used to Levels of Lead (P) in Farmer’s Blood in Bangka District - Roby Fauzan Samsulaga; Wimpy Wimpy (Jurnal Surya Medika (JSM), 2022)
Farmers exposed to pesticides. It can cause pollution and residues. Pesticides contain Plumbum (Pb). Pb can effect to the hematopoietic, digestive, urinary, kidney, central nervous, reproductive, cardiac and endocrine systems. The purpose was to determine the relationship between types of pesticides based on the active compounds used on Pb levels in the farmers blood in Bangka district. This research is analytic observational with cross sectional approach. The subjects were 20 farmers exposed to pesticides and with criteria based on the questionnaire in Bangka district. Use quota sampling. Primary data, namely measurement of blood lead levels using the Inductively Coupled Plasma - Mass Spectrophotometry (ICP-MS) method and types of pesticides based on active compounds. Level of Pb in the farmer's blood was the highest level of 6.6 g/dL and the lowest level of 1.7 g/dL with an average of 4.1 g/dL and still within normal limits. Respondents who used organophosphate pesticides found the highest levels of 6.6 g/dL and the lowest levels of 2.5 g/dL with an average of 4.36 g/dL. Respondents who used carbamate pesticide obtained the highest level of 5.1 g/dL and the lowest level of 1.7 g/dL with an average of 4.06 g/dL. The results from the ANOVA test with an F count of 4.789 and a significance level of probability 0.032 < 0.05, there was a significant relationship between types of pesticides based on the content of active compounds used by farmers on blood lead levels in Bangka district.